Hubungan Penggunaan Kontrasepsi Implant Dengan Kenaikan Berat Badan Pada Wanita Usia Subur di Puskesmas Pardamean Kecamatan Siantar Marihat Kota Pematangsiantar Tahun 2023 - Julipa Siringo Ringo; Asnita Sinaga (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Contraceptive use is one of the variables that influences fertility. Contraception can be interpreted as an action that helps married couples to avoid unwanted pregnancies, get the birth they really want, regulate the interval between pregnancies, control the timing of pregnancy and relate to the age of husband and wife and determine the number of children in the family (Hasliana, 2020) Program targets KB is a couple of childbearing age (PUS) which is more focused on the group of women of childbearing age (WUS) who are in the age range of 20-35 years. Family planning services are carried out through the use or use of contraception (Ministry of Health of the Republic of Indonesia, 2015). Based on the comparison of the Chi-Square Calculation with the Chi-Square table, the results of the analysis obtained a Chi-Square Calculation of 47.0 while it is known that the Chi-Square Table value for α = 5% (0.05), db = 1 is 3,481. Because the Chi-Square Square Count > Chi-Square Table then Ho is rejected. From the analysis results, it is known that the Asymp.Sig value is 0.005, where this value is smaller than the value of α = 5% (0.05). Thus it was decided to reject Ho. This means that the conclusion is that there is a relationship between the use of implant contraception and weight gain in family planning acceptors at the Pardamean Community Health Center, Siantar Marihat District, Pematangsiantar City in 2023. Based on the initial survey conducted at the Pera clinic, there were 10 mothers who used contraceptive implants, of these 10 people, 6 people experienced weight gain and 4 people did not experience weight gain, so from here the researchers were interested in taking the title "Relationship with Use "Contraceptive Implant with Weight Gain in Women of Childbearing Age at the Pardamean Health Center, Siantar Marihat District, Pematangsiantar City in 2023."